OPTIMALISASI PRAKTIK MANAJEMEN PEMASARAN MELALUI PEMANFAATAN TEKNOLOGI DIGITAL DI KALANGAN UMKM DESA PENUJAK, LOMBOK TENGAH - Kembang, Lale Puspita; Kalbuadi, Amirudin; Samsumar, Lalu Delsi; Zaenudin, Zaenudin (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
This community service aims to optimize marketing management practices among Micro, Small and Medium Enterprises (UMKM) in Penujak Village, Central Lombok, through the use of digital technology. Penujak Village as an area with growing economic potential needs support in facing increasingly fierce market competition. However, UMKM in this village often face challenges in implementing digital technology in their marketing practices due to limited resources and knowledge. This service will provide training and guidance on the use of digital technology in marketing strategies. Topics that will be raised include an introduction to digital technology in marketing management, digital-based marketing strategies for UMKM, data analysis to optimize marketing, and the importance of digital branding in differentiating businesses in a competitive market. In addition, this dedication will also discuss the use of social media in marketing practices, the need for data security and privacy in digital marketing, and how to measure digital marketing performance for future strategy adjustments. The results of this service are expected to provide new insights and skills for UMKM in Penujak Village, so that they can effectively utilize digital technology to increase business success and contribute to the village's overall economic growth.